Influence of electric conversion on the rollover safety of a large passenger vehicle - Raats, Daniel James (Stellenbosch : Stellenbosch University, 2025)
Raats, D. J. 2025. Influence of electric conversion on the rollover safety of a large passenger vehicle. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/50935042-7304-4f84-8cd8-0d083bc0dc52